Mixed-Race Identity Black and Maliseet: My Personal Narrative - McCarthy, Mary (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2014)
DIVIDED INTO FOUR SECTIONS, THIS IS A FIRST-PERSON NARRATIVE of my experiences of identity and the subsequent challenges that I have come to grapple with and reflect upon. The first section will explain my personal identity and will give some background to my life and my formative years. The second section will define my ancestral journey, specifically discussing my great aunt’s genealogical notes and how they are interpreted and blended with my personal experience. The third section follows my spiritual journey and how I came to enter doctoral work. Here I will discuss my hidden and suppressed mixed-race identity and why my extended family’s identity has been elided and silenced. The final section will consider some basic and thought-provoking questions that I am attempting to answer as a person of colour and as a settler of colour on the stolen land called Turtle Island. I conclude with a discussion of how colonization has played a role in creating division and contributes to the fractured relationships among contemporary black and Indigenous communities in New Brunswick.